Reconceptualizing Development: A Linkages-of-Capital Approach (Global Journal of Human-Social Science, 2016)
Current theorizing and measurement do not really capture the multidimensional nature of development. The received wisdom fuelling development efforts has highlighted the importance of technological accumulation (Bell and Pavitt 1997), economic modeling (Zafirovski 1999), people's participation (Redclift 1992), bilateralism and multilateralism via trading blocs (Riley 1998), structural adjustment and the importance of contemporary knowledge management. (Jayarajah and Branson 1995). The major deficiency of these approaches is that they have largely focused on one aspect of development and the resultant practices have spawned a variety of destabilizing and decivilizing processes which continue to escalate: richpoor gaps, gender, social class, religious geographic inequalities and social problems. These have been further aggravated by materialist values which usually accompany capitalist-driven development.
Keywords: structural adjustment; technological accumulation; contemporary knowledge management